Research on Homework Design for the Integration of “Teaching, Learning, and Assessment” in Junior Secondary Mathematics Based on Backward Design - Yan, Fangfang (Journal of Educational Research and Policies, 2026)
Against the backdrop of the full implementation of the Compulsory Education Mathematics Curriculum Standards (2022 Edition) and the continued deepening of the “double reduction” policy, the competency-oriented education reform calls for a transformative shift in junior secondary mathematics homework design—from mechanical training toward quality-oriented education. The concept of “integration of teaching, learning, and assessment” emphasizes the alignment of goals and the seamless integration of teaching, learning, and evaluation throughout the process, providing a key leverage point to address the persistent challenges in current junior secondary homework design. Focusing on issues such as vague objectives and disconnection between assessment and instruction in existing mathematics homework design, this paper proposes a strategic framework based on backward design, centered on four core elements: “precise goal specification, explicit rubrics, structured tasks, and feedback-driven learning”. The aim is to offer concrete, practice-based references for in-service junior secondary mathematics teachers to optimize their homework design strategies.